Towards Effective Participatory Decision-Making on Climate-Smart Agriculture (CSA) Technologies: A Case Study of Rohal Suong Climate-Smart Village, Battambang Province, Cambodia - Eam, Dyna; Emdin, Fiona; Kura, Yumiko (2018)
Under the Climate-Smart Village (CSV) program of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), the village of Rohal Suong in Battambang Province was selected to be the first CSV in Cambodia. This provides the local community with an opportunity to identify and enhance existing practices, which can be classified as climate-smart agriculture (CSA) interventions, and to test new technologies that it can adopt. Those that were deemed appropriate as climate adaptation measures could then be out-scaled and upscaled in other places and in various levels. In this regard, a series of activities to support the participatory prioritization and selection of CSA technologies and practices (CSA T&P) was organized and participated by various stakeholder groups in Rohal Suong. These activities helped the community representatives identify the CSA T&Ps that could best improve their lives and meet their needs. As part of the CSA prioritization process, the representatives ensured that technologies and practices are relevant to the local context and are publicized for review and revision. The community workshop sessions considered the various issues within the community, especially those that affect different genders and people of lower socioeconomic status. Using Rohal Suong as an example of effective participatory priority setting, the researchers propose a procedural guide for the participatory prioritization of CSA T&P, which can guide the scaling process in other rural communities of Cambodia.